Think Pair Share (TPS) Integrated with Reading Questioning Answering (RQA): How Impact on Biological Literacy? - Rizhal Hendi Ristanto; Sri Rahayu; Adinda Maulidia (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
In this modern era, students who are literate are needed, namely those who understand scientific facts and their application to everyday life. Biology is subject that is needed in everyday life, so it is necessary for students to have a high level of biological literacy. One way to improve biological literacy is by applying cooperative and constructive learning models, namely Think Pair Share combined with Reading Questioning Answering. This study aims to determine the effect of the Think Pair Share (TPS) Learning Model combined with Reading Questioning Answering (RQA) on the Biological Literacy of Students at SMAN 13 Jakarta on the reproductive system. The research was conducted in May 2023 using a quasi-experimental research method with a pretest-posttest control group design. The research sample was selected by simple random sampling. The prerequisite test used is the normality test with the Kolmogorov-Smirnov test and the homogeneity test using the F test. Statistical hypothesis test with the independent t-test obtained the results of accept H0 at α = 0.05, which means that there is no influence of the Think Pair Share (TPS) learning model combined with Reading Questioning Answering (RQA) Biological Literacy’s students on reproductive system.